2017
DOI: 10.1111/ijfs.13600
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterisation and α‐amylase inhibitory activity of tea polysaccharides under simulated salivary, gastric and intestinal conditions

Abstract: Summary Tea polysaccharides (TPS) are one of the main components of tea with various bioactivities. Digestion could result in the changes of the physicochemical properties and bioactivities of polysaccharides. The objective of this study was to determine the changes in physicochemical properties and α‐amylase inhibitory activities of TPS after simulated digestion. The structure of TPS determined by UV, IR and SEM showed that no obvious changes after salivary digestion, but significant changes after gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…where ETPS and XTPS were more obvious, indicated that the reduction of metallic elements might release more carboxyl group. C-H absorption peaks were at 1,310-1,330 cm −1 were C-H absorption peaks (Cai et al, 2013;Li et al, 2018), where the absorption peak of the complex was obviously weaker than that of the natural polysaccharide, and the absorption peak of TPSII almost disappeared.…”
Section: Ft-ir Spectroscopic Characteristicsmentioning
confidence: 98%
“…where ETPS and XTPS were more obvious, indicated that the reduction of metallic elements might release more carboxyl group. C-H absorption peaks were at 1,310-1,330 cm −1 were C-H absorption peaks (Cai et al, 2013;Li et al, 2018), where the absorption peak of the complex was obviously weaker than that of the natural polysaccharide, and the absorption peak of TPSII almost disappeared.…”
Section: Ft-ir Spectroscopic Characteristicsmentioning
confidence: 98%
“…Previous studies have shown that the pH, bile salts and digestive enzymes in simulated digestive juices could alter their physicochemical properties, such as molecular weight, viscosity, chemical composition, surface morphology and conformation, as well as their biological activities, such as antioxidant activity and the inhibitory activities of α‐amylase and α‐glucosidase. (Hu et al ., 2013; Chen et al ., 2016; Cong et al ., 2018; Li et al ., 2018; Zhu, 2018). These parameters included mainly the pH and duration of digestion steps, number and type of digestive enzymes used, stirring/stirring speed and amount of polysaccharide sample.…”
Section: Overview Of Polysaccharide’s In Vitro Digestion Simulationmentioning
confidence: 99%
“…And the inhibitory effects of MLP-2 digestion fractions against the digestive enzymes were higher than those of polysaccharide fractions from mulberry fruit (Chen et al, 2016b). Polysaccharides could display α-amylase and α-glucosidase inhibitory action by physical interference and the direct binding with the digestive enzymes, which were closely dependent on their structure, conformation, monosaccharide proportion, chemical compositions and molecular weight distribution (Chen et al, 2016b, Nsor-Atindana, et al, 2012Li et al, 2018a;Chen et al, 2017;Yang et al, 2019;Kasipandi et al, 2019). In our study, the chemical compositions (sugar, uronic acid and protein contents), monosaccharide proportion and molecular weight of MLP-2 were all altered after the sequential simulated salivary, gastric and intestinal digestion, which might explain why MLP-2 did not inhibit the activities of α-amylase and α-glucosidase while its digested fractions displayed significantly enhanced inhibition against the digestive enzymes.…”
Section: Morphological Properties Analysismentioning
confidence: 99%